Study of the fungicidal effect of the chimeric form of interferon alpha-2b in relation to fungi-pathogens of plants and animals - V. S. Maslennikova; C. M. Miroshnichenko; E. V. Shelikhova; K. A. Tabanyukhov; I. Yu. Deulin; M. B. Pykhtina (Сибирский научный медицинский журнал, 2024)
The purpose of this study is to evaluate the fungicidal effect of a chimeric form of recombinant interferon alpha-2b, fused with human apolipoprotein A-I, obtained by biosynthesis in the yeast Pichia рastoris, against significant fungal pathogens – pathogens of human and plant diseases.Material and methods. The fungicidal activity of the chimeric cytokine was assessed using the agar block method against fungal pathogens: Alternaria alternata, Fusarium oxysporum, Aspergillus spp. and Penicillum spp. The fungicidal effect was assessed visually and by microscopy of a section of the fungal body stained with methylene blue, the germination of fungal spores – by subculture, the cytotoxicity of interferon preparations – on Vero cell culture.Results and discussion. The studied recombinant interferons suppress the growth and reproduction of pathogenic fungi. Chimeric IFN has the greatest effect against pathogenic fungi A. alternate, Penicillum at a concentration of 15 ng/ml; inhibition of sporulation of fungi F. oxysporum and Aspergillus up to 87 % is achieved at a concentration of 150 ng/ml. The cytotoxicity of the new chimeric cytokine is 5,8 μg/ml, which is significantly more than toxic concentrations for fungi.Conclusions. The chimeric form of interferon alpha-2b can be used as an immunotherapeutic agent with fungicidal activity.